Effect of a Heat Wave on Lentil Grown under Free‐Air CO2 Enrichment (FACE) in a Semi‐Arid Environment. Issue 2 (1st March 2018) - Bourgault, M.; Löw, M.; Tausz‐Posch, S.; Nuttall, J. G.; Delahunty, A. J.; Brand, J.; Panozzo, J. F.; McDonald, L.; O'Leary, G. J.; Armstrong, R. D.; Fitzgerald, G. J.; Tausz, M.
Abstract : Atmospheric CO2 concentrations have been increasing from ∼280 to 405 mmol mol −1 air from the preindustrial era until now. As this rise is a major driver for global warming and increasing variability in weather patterns, it is predicted that the frequency and duration of heat waves will continue to increase in many arable regions during this century. Lentil ( Lens culinaris Medik.) is a cool‐season crop whose production has recently expanded into areas where it is subject to high temperature stress during pod filling (e.g., Australia). The objective of this experiment was to determine whether growth at elevated atmospheric CO2 concentrations (e[CO2 ], imposed by free‐air CO2 enrichment [FACE]) is able to compensate for the negative impact of a 3‐d heat wave event imposed at the flat pod stage on two lines of lentil. Grain yield under e[CO2 ] subjected to the heat wave were equivalent to grain yield under ambient without the heat wave event. The heat wave reduced grain yield by 33%, but this was not made more or less severe by e[CO2 ]. This reduction was attributed to a small decrease in aboveground biomass (6%) and a larger decrease in harvest index (16%) due to the heat wave event. The number of pods and grains per square meter were reduced by the heat wave (29–32%), whereas seed size was not affected. The effects of the heat wave during the event were evident on the foliar canopy temperature measured with an infrared thermometer, which increased by 6°C, and on the electron transport rate calculated from the quantum efficiency of photosystem II obtained with chlorophyll fluorescence measurements.